Preparation method of adsorbent for groundwater remediation

By preparing nanozeolite seed crystalline silicon spheres with multi-stage pore structures, the problem of poor adsorption performance is solved, efficient pollutant adsorption and stable performance is achieved, and it is suitable for groundwater repair.

CN119869445APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311387972.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The adsorption performance of nanozeolite seed-crystalline silicon spheres is poor, resulting in poor results in groundwater repair.

Method used

By preparing nanozeolite seed-crystallized silicon spheres, hydrothermal crystallization and reflux treatment are used to form adsorbents with multi-stage pore structures to improve their adsorption performance.

Benefits of technology

The contaminant adsorption rate and adsorption amount of nanozeolite seed silicon spheres is significantly improved, and the preparation process is simple and easy to perform, and the product has high stability and reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869445A_ABST
    Figure CN119869445A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of groundwater remediation, and particularly discloses a preparation method of an adsorbent for groundwater remediation. Comprising the following steps: (1) preparing nano zeolite sol; (2) preparing mesoporous silica solid powder; (3) preparing nano zeolite seed crystal silicon balls; (4) preparing an adsorbent finished product, namely hierarchical pore zeolite microspheres; and (3) putting a certain amount of nano zeolite seed crystal silicon spheres prepared in the step (3) into a certain amount of clear growth liquid with the mass ratio of tetrapropylammonium hydroxide to water to absolute ethyl alcohol being (0.6-0.8): (7-8): (1.3-1.5), carrying out hydro-thermal treatment in a reaction kettle at a certain temperature for a certain time, washing with 0.1 mol / L ammonia water for multiple times, washing with deionized water for multiple times to obtain hollow zeolite microspheres, and drying to obtain the hollow zeolite microspheres. And after airing at 100 DEG C, calcining in a muffle furnace for 6 hours in an air atmosphere at 550 DEG C to remove the organic template agent to obtain a solid powdery product which is an adsorbent finished product. The prepared adsorbent can be repeatedly used and is excellent in adsorption performance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of groundwater remediation, and in particular relates to a method for preparing an adsorbent for groundwater remediation. Background Art

[0002] Groundwater is an important water source, but due to the influence of human activities such as over-exploitation, industrialization and agriculturalization, groundwater has become a resource that is easily polluted. At present, groundwater pollution has become one of the common environmental problems in the world. Groundwater pollution seriously threatens people's health and living environment. The types of pollutants and the corresponding degree of harm are complex and diverse. These include pollutants from different sources such as organic matter, heavy metals, pesticides, etc., and the nature of the pollution is very complex, often causing direct or indirect harm to the human body. With the improvement of artificial groundwater recharge technology and the increase in groundwater extraction, the problem of groundwater pollution will become more prominent. Therefore, protecting groundwater resources and reducing pollution have become important issues that need to be urgently solved in today's society.

[0003] Existing groundwater remediation technologies include physical, chemical and biological methods. Physical methods mainly achieve pollutant removal through the effects of medium mass transfer and medium permeability, such as extraction method, gas conduction method, electromigration method, etc. This method cannot completely remove pollutants and has a long cycle. It generally only plays a synergistic role when used in combination with other remediation technologies. Chemical methods use chemical reactions and chemical changes to degrade or transform pollutants, including reduction, oxidation, heating and other methods, such as chemical reduction method, chemical oxidation method, etc. This method can effectively degrade pollutants but there are problems such as large resource input and great impact on the environment. The biological method is easy to operate, will not form secondary pollution, and can degrade specific pollutants. It has good applicability. The biological method includes two types: natural remediation and artificial remediation, such as plant absorption and soil anaerobic reaction.

[0004] Adsorption has attracted much attention as an effective and sustainable technology. Adsorption remediation technology is a technology that uses adsorbent substances to adsorb harmful substances in groundwater, transfer them to the surface of the adsorbent and fix them on the adsorbent, so as to purify the groundwater. Adsorption is a combined physical and chemical remediation technology, which belongs to the category of chemical remediation technology. The adsorption behavior of adsorbents in groundwater is a physical process, but this process involves the interaction between adsorbents and pollutants, and there are factors of chemical reaction. Therefore, adsorption can be regarded as a combination of physical and chemical methods, which reflects both physical properties and chemical reaction mechanisms. Adsorbents have the advantages of high efficiency, concentration, recycling, and will not cause secondary pollution. They can have a good removal effect on various types of pollutants. Compared with other methods, adsorption remediation technology has many advantages, such as easy operation, stable effect, and the ability to selectively remove specific pollutants. It can remove pollutants without destroying the original environmental properties of groundwater. However, adsorption cannot achieve the effect of complete treatment. It generally needs to be used in combination with other methods to better control and repair groundwater pollution.

[0005] In recent years, new adsorbents have adopted the principle of functional modification, which increases the affinity and selectivity of adsorbents with organic matter, greatly improving the adsorption capacity and efficiency. The application of nanomaterials in groundwater remediation has gradually matured, and their unique adsorption properties and catalytic degradation effects are more effective than traditional adsorbent materials. However, traditional adsorbents have problems such as low adsorption efficiency and poor selectivity. Nano-zeolite seeded silica spheres, as a new adsorbent material that has attracted much attention, have the advantages of good adsorption performance, high stability and renewability. However, due to the limitations of surface charge properties, the adsorption performance of nano-zeolite seeded silica spheres is not ideal. Therefore, if the nano-zeolite seeded silica spheres are compounded with polycationic electrolytes to form cationic regions on the surface, the adsorption performance of the nano-zeolite seeded silica spheres will be greatly improved.

[0006] Chinese invention patent CN110586033A discloses a method for preparing a mixed carbon-based adsorbent material for groundwater remediation, which uses camellia oleifera shells and phosphoric acid as raw materials, and forms an adsorbent material through steps such as impregnation, carbonization, and activation. Chinese invention patent CN113181886A prepares a new polypyrrole-loaded carbon-containing matrix adsorbent material by in-situ polymerization, which is used to remove nitrates from groundwater. Chinese invention patent CN112755962A uses a coprecipitation method to prepare chitosan-modified magnetic biochar materials to remove three heavy metal ions of lead, copper, and cadmium from groundwater. The present invention uses mesoporous silica microspheres containing nano-zeolite seeds as adsorbents. This adsorbent has a larger effective surface area and a faster mass transfer kinetic response, and the morphology and pore structure of the microspheres can be controlled by adjusting the reaction conditions and component ratios, thereby increasing the adsorption rate and adsorption amount of pollutants. At the same time, the preparation process is simple and easy, the resulting product has excellent physical and chemical properties, and can avoid the problem of nanoparticle agglomeration. Therefore, compared with the adsorbents in the aforementioned patents, the present invention has a more efficient pollutant adsorption capacity and a more stable performance, and can be prepared into a reusable adsorbent. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing an adsorbent for groundwater remediation, which effectively solves the problem of poor adsorption performance of current nano-zeolite seeded silicon balls.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0009] A method for preparing an adsorbent for groundwater remediation comprises the following steps:

[0010] S1, preparing nano zeolite sol;

[0011] A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed and stirred vigorously at room temperature to obtain a transparent colloidal solution, which is then refluxed in an oil bath at 90-110°C for 30-40 hours to obtain product I. The obtained product I is repeatedly centrifuged and finally ultrasonically dispersed to obtain a zeolite colloidal solution, and the pH value is adjusted to 9-10 for use.

[0012] S2, preparing mesoporous silica solid powder;

[0013] Weigh a certain amount of deionized water and isopropanol, mix them evenly at room temperature, add a certain amount of hexadecylamine, dissolve them with ultrasound assistance, add a certain amount of ammonia water while stirring, and inject a certain amount of tetraethoxysilane at one time, stop stirring after 30 seconds, and let it stand at room temperature for 24 hours to obtain product II.

[0014] The product II was separated by centrifugation and ultrasonic dispersion to obtain the product III.

[0015] The product III was washed until the pH value was close to neutral, then dried at 60° C. for 12 h, and then placed in a muffle furnace at 600° C. and calcined in an air atmosphere for 6 to 8 h to remove the organic template, thereby obtaining a mesoporous silica solid powder.

[0016] S3, preparing nano-zeolite seeded silicon balls;

[0017] The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, and after gentle stirring and adsorption for 1 to 2 hours at room temperature, it is washed with deionized water and centrifuged several times to remove excess polycation electrolyte to obtain cation-modified mesoporous silica microspheres.

[0018] The modified mesoporous silica microspheres were immersed in 1% nano-zeolite gel solution, gently stirred for a period of time, washed with 0.1 mol / L ammonia water and centrifuged several times, and then dried at 60°C to obtain nano-zeolite seeded silica spheres.

[0019] S4, preparing finished adsorbent product - hierarchical pore zeolite microspheres;

[0020] A certain amount of nano-zeolite seeded silicon balls prepared in step S3 are placed in a certain amount of clarified growth liquid with a mass ratio of TPAOH:H2O:EtOH=0.6-0.8:7-8:1.3-1.5, and after hydrothermal treatment at a certain temperature in a reactor for a certain time, they are washed multiple times with 0.1 mol / L ammonia water, and then washed multiple times with deionized water to obtain hollow zeolite microspheres. After drying at 100°C, they are calcined in a muffle furnace at 550°C in an air atmosphere for 6 hours to remove the organic template, and the obtained solid powder product is the finished adsorbent product - hierarchical pore zeolite microspheres.

[0021] Further, in step S1, the molar ratio of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=8-10:20-30:450-550:80-120.

[0022] Furthermore, in step S1, the duration of the vigorous stirring at room temperature is 20 to 30 hours.

[0023] Furthermore, in step S1, the rotation speed of the centrifugal separation is 8000-12000 rpm, the centrifugal time is 40-90 min; and the ultrasonic dispersion time is 15-30 min.

[0024] Furthermore, in step S1, ammonia water is used to adjust the pH value of the zeolite colloidal solution.

[0025] Furthermore, in step S2, the volume ratio of the deionized water to isopropyl alcohol is 1:1 to 1.2.

[0026] Furthermore, in step S2, the mass fraction of the ammonia water is 25% to 28%.

[0027] Further, in step S2, ethanol and deionized water are used to adjust the pH value of the product III.

[0028] Further, in step S2, the heating rate of the muffle furnace is 2°C / min; and in step S4, the heating rate of the muffle furnace is 5°C / min.

[0029] Furthermore, in step S3, the solid-to-liquid mass ratio of the mesoporous silica solid powder to the polydimethyldiisopropylammonium chloride aqueous solution is 1:10.

[0030] Furthermore, in step S3, the pH value of the nano-zeolite colloid is 9.5.

[0031] Furthermore, in step S4, the temperature of the hydrothermal treatment is 80-150° C., and the duration is 1-3 days.

[0032] Furthermore, in step S2, the rotation speed of centrifugal separation of product II is 8000-12000 rpm, the centrifugal time is 5-10 min, and the ultrasonic dispersion time is 15-30 min.

[0033] Furthermore, in step S3, the number of centrifugation is 3 to 5 times, the centrifugal speed is 8000 to 12000 rpm, and the centrifugal time is 5 to 10 minutes.

[0034] Furthermore, in step S3, the modified mesoporous silica microspheres are immersed in a 1% nano-zeolite gel solution and gently stirred for 1 to 2 hours.

[0035] Further, in step S4, after the hydrothermal treatment, the zeolite microspheres are washed with 0.1 mol / L ammonia water for 3 to 5 times and then washed with deionized water for 2 to 3 times to obtain hollow zeolite microspheres.

[0036] The beneficial technical effects of the present invention are:

[0037] (1) The production process is simple and easy.

[0038] The present invention adopts a hydrothermal crystallization method to prepare a transparent colloidal solution, and obtains an adsorbent for groundwater remediation through a series of reaction steps. The entire preparation process is simple and easy, and the morphology and pore structure of the microspheres can be controlled by adjusting the reaction conditions and the component ratio.

[0039] (2) The adsorbent prepared by the present invention has high pollutant adsorption capacity and stable performance.

[0040] The adsorbent prepared by the invention not only has a highly efficient pollutant adsorption capacity, but also exhibits good stability and can be reused.

[0041] (3) The pore structure of the adsorbent prepared by the present invention is evenly distributed.

[0042] The present invention can form a uniformly distributed zeolite membrane to avoid the problem of nanoparticle agglomeration by adjusting the reaction conditions and component ratios, shorten the diffusion path of pollutant molecules, and reduce mass transfer resistance, thereby effectively improving the adsorption rate and adsorption amount of pollutants.

[0043] (4) The adsorbent prepared by the present invention has a larger effective surface area and a faster mass transfer kinetic response.

[0044] The adsorbent prepared by the present invention has micropores, mesopores and macropores at the same time, and can provide a larger effective surface area and a faster mass transfer kinetic response.

[0045] In summary, the present invention has the advantages of simple and easy preparation process, and the prepared adsorbent has many advantages such as high pollutant adsorption capacity and stable performance, uniformly distributed pore structure, large effective surface area and fast mass transfer kinetic response. Compared with the prior art, the present invention has broader application prospects and is a groundwater remediation adsorbent with important application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0047] Figure 1 The scanning electron microscope image (a) and the transmission electron microscope image (b) of the silicalite-1 zeolite prepared in Comparative Example 1 of the present invention;

[0048] Figure 2 is the XRD spectrum of silicalite-1 zeolite prepared in Comparative Example 1 of the present invention;

[0049] Figure 3 is a particle size distribution diagram of silicalite-1 zeolite prepared in comparative example 1 of the present invention in an aqueous phase;

[0050] Figure 4 is a scanning electron microscope image of the mesoporous silica microspheres prepared in Comparative Example 2 of the present invention;

[0051] Figure 5 is a particle size distribution diagram of mesoporous silica microspheres prepared in comparative example 2 of the present invention in an aqueous phase;

[0052] Figure 6 The scanning electron microscope images (a, b) and the transmission electron microscope image (c) of the adsorbent product I prepared in Example 1 of the present invention are shown;

[0053] Figure 7 The scanning electron microscope images (a, b) and the transmission electron microscope image (c) of the adsorbent finished product II prepared in Example 2 of the present invention are shown;

[0054] Figure 8 is a scanning electron microscope image of the adsorbent product III prepared in Example 3 of the present invention;

[0055] Fig. 9 is a scanning electron microscope image of the adsorbent product IV prepared in Example 4 of the present invention;

[0056] Fig.10 is a scanning electron microscope image of the adsorbent product V prepared in Example 5 of the present invention;

[0057] Fig.11 is a bar graph of the removal rate of MTBE by different adsorbent materials in Test Example 1 of the present invention;

[0058] Fig.12 It is a fitting diagram of the MTBE adsorption process of the adsorbent finished product and silicalite-1 zeolite in Test Example 2 of the present invention. DETAILED DESCRIPTION

[0059] A method for preparing an adsorbent for groundwater remediation comprises the following steps:

[0060] S1, preparing nano zeolite sol;

[0061] A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed, wherein the molar ratio of the tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=8-10:20-30:450-550:80-120.

[0062] The mixture was stirred vigorously at room temperature for 20 to 30 h to obtain a transparent colloidal solution, which was then refluxed in an oil bath at 90 to 110 °C for 30 to 40 h to obtain product I.

[0063] The obtained product I is repeatedly centrifuged (8000-12000 rpm for 40-90 min), and finally ultrasonically dispersed for 15-30 min to obtain a zeolite colloidal solution, and the pH value is adjusted to about 9-10 with ammonia water for later use.

[0064] S2, preparing mesoporous silica solid powder;

[0065] Weigh a certain amount of deionized water and isopropanol, the volume ratio of which is 1:1-1.2, mix them evenly at room temperature, add a certain amount of hexadecylamine, dissolve them with ultrasound assistance, add a certain amount of ammonia water under stirring, the mass fraction of which is 25%-28%, and inject a certain amount of tetraethoxysilane at one time, stop stirring after 30 seconds, and let stand at room temperature for 24 hours to obtain product II.

[0066] The product II is centrifuged (8000-12000 rpm for 5-10 min) and ultrasonically dispersed for 15-30 min to obtain the product III.

[0067] The product III was washed with ethanol and deionized water respectively until the pH was close to neutral, then dried at 60°C for 12 hours, and then placed in a muffle furnace at 600°C with a heating rate of 2°C / min. The product was calcined in an air atmosphere for 6 to 8 hours to remove the organic template to obtain a mesoporous silica solid powder.

[0068] S3, preparing nano-zeolite seeded silicon balls;

[0069] The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, wherein the solid-liquid mass ratio of the mesoporous silica solid powder to the polydimethyl diisopropyl ammonium chloride aqueous solution is 1:10. After gentle stirring and adsorption for 1 to 2 hours at room temperature, the powder is washed with deionized water and centrifuged for 3 to 5 times (centrifuged at 8000 to 12000 rpm for 5 to 10 minutes) to remove excess polycation electrolyte, thereby obtaining cation-modified mesoporous silica microspheres.

[0070] The modified mesoporous silica microspheres were immersed in a 1% nano-zeolite gel solution with a pH value of about 9.5, and gently stirred for 1 to 2 hours. After that, they were washed with 0.1 mol / L ammonia water and centrifuged for 3 to 5 times (8000 to 12000 rpm for 5 to 10 minutes), and then dried at 60°C to obtain nano-zeolite seeded silicon spheres.

[0071] S4, preparing finished adsorbent product - hierarchical pore zeolite microspheres;

[0072] A certain amount of the nano-zeolite seeded silicon ball sample prepared in step S3 is placed in a certain amount of clarified growth liquid with a mass ratio of TPAOH:H2O:EtOH=0.6-0.8:7-8:1.3-1.5, and after hydrothermal treatment at 80-150°C in a reactor for 1-3 days, it is washed with 0.1 mol / L ammonia water for 3-5 times, and then washed with deionized water for 2-3 times to obtain hollow zeolite microspheres.

[0073] Then, after drying at 100° C., the organic template is removed by calcining in a muffle furnace at 550° C. in an air atmosphere for 6 hours. The heating rate of the muffle furnace is 5° C. / min. The obtained solid powder product is the finished adsorbent - hierarchical pore zeolite microspheres.

[0074] The adsorbent prepared by the invention has macroporous and mesoporous structures, and nano-zeolite seeded functional units are introduced on the surface. The adsorbent has high efficient adsorption capacity and high stability, and is suitable for the remediation of pollutants in groundwater.

[0075] The present invention adopts hydrothermal crystallization, reflux treatment and centrifugal dispersion treatment to produce an adsorbent for groundwater remediation, which has the following beneficial effects:

[0076] (1) The production process is simple and easy.

[0077] The present invention adopts a hydrothermal crystallization method to prepare a transparent colloidal solution, and obtains an adsorbent for groundwater remediation through a series of reaction steps. The entire preparation process is simple and easy, and the morphology and pore structure of the microspheres can be controlled by adjusting the reaction conditions and the component ratio.

[0078] (2) The adsorbent prepared by the present invention has high pollutant adsorption capacity and stable performance.

[0079] The adsorbent prepared by the invention not only has a highly efficient pollutant adsorption capacity, but also exhibits good stability and can be reused.

[0080] (3) The pore structure of the adsorbent prepared by the present invention is evenly distributed.

[0081] The present invention can form a uniformly distributed zeolite membrane to avoid the problem of nanoparticle agglomeration by adjusting the reaction conditions and component ratios, shorten the diffusion path of pollutant molecules, and reduce mass transfer resistance, thereby effectively improving the adsorption rate and adsorption amount of pollutants.

[0082] (4) The adsorbent prepared by the present invention has a larger effective surface area and a faster mass transfer kinetic response.

[0083] The adsorbent prepared by the present invention has micropores, mesopores and macropores at the same time, and can provide a larger effective surface area and a faster mass transfer kinetic response.

[0084] In summary, the present invention has the advantages of simple and easy preparation process, and the prepared adsorbent has many advantages such as high pollutant adsorption capacity and stable performance, uniformly distributed pore structure, large effective surface area and fast mass transfer kinetic response. Compared with the prior art, the present invention has broader application prospects and is a groundwater remediation adsorbent with important application value.

[0085] The present invention is further described in detail below in conjunction with comparative examples, embodiments and test examples.

[0086] Comparative Example 1: The intermediate product silicalite-1 zeolite of the present invention is prepared by hydrothermal synthesis, and the preparation steps are as follows:

[0087] (1) Prepare a reaction solution.

[0088] Tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol were mixed in a molar ratio of TPAOH:TEOS:H2O:EtOH=9:25:480:100, and the mixed solution was vigorously stirred at room temperature for 24 hours to obtain a transparent colloidal solution.

[0089] (2) Reflux reaction

[0090] The colloidal solution was placed in an oil bath and refluxed at 100° C. for 36 h to obtain a nano-zeolite product.

[0091] (3) Separation and cleaning.

[0092] The obtained nano-zeolite product was repeatedly centrifuged (10000 rpm for 60 min), then ultrasonically dispersed for 20 min, and washed with deionized water until the pH was close to neutral.

[0093] (4) Drying treatment.

[0094] Dry in an oven at 100°C for 12 hours.

[0095] (5) Calcination treatment.

[0096] The dried sample was placed in a muffle furnace at 550°C (heating rate of 5°C / min) and calcined in an air atmosphere for 6 hours to remove the organic template, and the obtained solid powder product was silicalite-1 zeolite.

[0097] The microstructure of silicalite-1 zeolite was observed using scanning electron microscopy and transmission electron microscopy. Figure 1 (a) and Figure 1 (b) as shown.

[0098] Figure 1 (a) and Figure 1 (b) shows that the silicalite-1 zeolite prepared by hydrothermal synthesis using TPAOH as a template is spherical, with a clean surface and a relatively uniform particle size distribution. The particle size range of the prepared silicalite-1 measured by Image J software is about 100nm.

[0099] In order to confirm the crystal structure of the prepared silicalite-1 zeolite, the XRD spectrum was further measured and analyzed and compared using JADE software. The results are shown in Figure 2 The results show that the prepared silicalite-1 has less impurity peak content, sharp peak shape, good crystallinity, and is consistent with the diffraction peaks of MFI zeolite at 2θ=7.8, 8.7, 23, 23.6, and 24.5°.

[0100] In order to prove the dispersibility of silicalite-1 zeolite in water phase, the particle size distribution of silicalite-1 zeolite in water phase was measured by dynamic light scattering method. Figure 3 The prepared silicalite-1 zeolite agglomerated into particles of 200.19 to 458.67 nm in water and could not be completely dispersed after repeated ultrasonic treatment.

[0101] Comparative Example 2: Preparation of the intermediate product of the present invention, solid powdered mesoporous silica microspheres (MS), the preparation steps are as follows:

[0102] (1) Prepare the colloidal solution.

[0103] Tetrapropylammonium hydroxide (TPAOH), tetraethoxysilane (TEOS), deionized water and anhydrous ethanol (EtOH) were mixed in a molar ratio of TPAOH:TEOS:H2O:EtOH=9:25:480:100, and stirred vigorously at room temperature for 24 hours to obtain a transparent colloidal solution.

[0104] (2) The zeolite colloidal solution was prepared by hydrothermal crystallization method.

[0105] The transparent colloidal solution obtained in step (1) is placed in an oil bath and refluxed at 100° C. for 36 hours to obtain a nano-zeolite product with a certain pore size and structure.

[0106] Then, the nano-zeolite product was repeatedly centrifuged (10000 rpm for 60 min) and ultrasonically dispersed for 20 min, and the nano-zeolite product was re-dispersed in deionized water to obtain a zeolite colloidal solution with a mass fraction of about 4.0%.

[0107] The pH value of the zeolite colloidal solution is adjusted to about 9.5 with ammonia water for later use.

[0108] (3) Preparation of mesoporous silica microspheres.

[0109] Weigh 100 mL of isopropanol and 90 mL of deionized water and mix them evenly at room temperature, add 1 g of hexadecylamine, dissolve it with ultrasound assistance, add 1.4 mL of 25%-28% ammonia water under stirring, inject 5.8 mL of tetraethoxysilane at one time, stop stirring after 30 seconds, and let it stand at room temperature for 24 hours to obtain product II.

[0110] The obtained product II was centrifuged (10000 rpm for 5 min) and ultrasonically dispersed for 20 min to obtain product III.

[0111] The product III was washed with ethanol and deionized water respectively until the pH was close to neutral, then dried at 60°C for 12 hours, and then placed in a muffle furnace at 600°C (heating rate of 2°C / min), and calcined in an air atmosphere for 6 hours to remove the organic template, thereby obtaining solid powdered mesoporous silica microspheres.

[0112] The surface morphology of mesoporous silica microspheres was observed using a scanning electron microscope (SEM). Figure 4 As shown. Figure 4 It can be seen that the average particle size of the mesoporous silica microspheres is 1 μm, the particle size distribution is narrow and the dispersibility is good.

[0113] The particle size distribution of mesoporous silica microspheres in water phase was determined by dynamic light scattering (DLS). Figure 5 As shown. Figure 5 It can be seen that the particle size distribution results measured by dynamic light scattering are similar to those of scanning electron microscopy, and the average particle size of mesoporous silica microspheres is 1.1 μm. Since the DLS method measures the hydration radius of mesoporous silica microspheres in solution, the measured results are slightly larger than the radius of SEM under dry conditions.

[0114] Example 1: Preparation of the adsorbent finished product I-multi-level pore zeolite microspheres I of the present invention, the preparation steps are as follows:

[0115] S1, preparing nano zeolite sol;

[0116] A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed, wherein the molar ratio of the tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=9:25:480:100.

[0117] The mixture was stirred vigorously at room temperature for 24 h to obtain a transparent colloidal solution, which was then refluxed in an oil bath at 100° C. for 36 h to obtain product I.

[0118] The obtained product I was repeatedly centrifuged (10000 rpm for 60 min), and finally ultrasonically dispersed for 20 min to obtain a zeolite colloidal solution with a mass fraction of about 4.0%, and the pH value was adjusted to about 9.5 with ammonia water for use.

[0119] S2, preparing mesoporous silica solid powder;

[0120] Weigh 90 mL of deionized water and 100 mL of isopropanol and mix them evenly at room temperature, add 1 g of hexadecylamine, dissolve it with ultrasound assistance, add 1.4 mL of 25%-28% ammonia water under stirring, and inject 5.8 mL of tetraethoxysilane at one time. Stop stirring after 30 seconds and let it stand at room temperature for 24 hours to obtain product II.

[0121] The product II was centrifuged (10000 rpm for 5 min) and ultrasonically dispersed for 20 min to obtain the product III.

[0122] The product III was washed with ethanol and deionized water respectively until the pH was close to neutral, then dried at 60°C for 12 hours, and then placed in a muffle furnace at 600°C with a heating rate of 2°C / min. The product was calcined in an air atmosphere for 6 hours to remove the organic template and obtain a mesoporous silica solid powder.

[0123] S3, preparing nano-zeolite seeded silicon balls;

[0124] The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, wherein the solid-liquid mass ratio of the mesoporous silica solid powder to the polydimethyl diisopropyl ammonium chloride aqueous solution is 1:10. After gentle stirring and adsorption for 1 hour at room temperature, the powder is washed with deionized water and centrifuged three times (centrifuged at 10000 rpm for 5 minutes) to remove excess polycation electrolyte, thereby obtaining cation-modified mesoporous silica microspheres.

[0125] The modified mesoporous silica microspheres were immersed in a 1% nano-zeolite gel solution with a pH value of about 9.5, and gently stirred for 1 hour. After that, they were washed with 0.1 mol / L ammonia water and centrifuged 3 times (10000 rpm for 5 minutes), and then dried at 60°C to obtain nano-zeolite seeded silicon spheres.

[0126] S4, preparing adsorbent finished product I - hierarchical pore zeolite microspheres I;

[0127] 0.1 g of the nano-zeolite seeded silicon spheres prepared in step S3 were placed in a clarified growth solution with a mass ratio of TPAOH:H2O:EtOH=0.75:7.77:1.48, and after hydrothermal treatment at 80°C in a reactor for 1 day, they were washed 3 times with 0.1 mol / L ammonia water and then washed 2 times with deionized water to obtain hollow zeolite microspheres.

[0128] Then, after drying at 100° C., the organic template is removed by calcining in a muffle furnace at 550° C. in an air atmosphere for 6 hours. The heating rate of the muffle furnace is 5° C. / min. The obtained solid powder product is the finished adsorbent I-multi-level porous zeolite microspheres I.

[0129] Example 2: Preparation of the adsorbent finished product II of the present invention - hierarchical pore zeolite microspheres II, the preparation steps are as follows:

[0130] S1, preparing nano zeolite sol;

[0131] A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed, wherein the molar ratio of the tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=9:25:480:100.

[0132] The mixture was stirred vigorously at room temperature for 24 h to obtain a transparent colloidal solution, which was then refluxed in an oil bath at 100° C. for 36 h to obtain product I.

[0133] The obtained product I was repeatedly centrifuged (10000 rpm for 60 min), and finally ultrasonically dispersed for 20 min to obtain a zeolite colloidal solution with a mass fraction of about 4.0%, and the pH value was adjusted to about 9.5 with ammonia water for use.

[0134] S2, preparing mesoporous silica solid powder;

[0135] Weigh 90 mL of deionized water and 100 mL of isopropanol and mix them evenly at room temperature, add 1 g of hexadecylamine, dissolve it with ultrasound assistance, add 1.4 mL of 25%-28% ammonia water under stirring, and inject 5.8 mL of tetraethoxysilane at one time. Stop stirring after 30 seconds and let it stand at room temperature for 24 hours to obtain product II.

[0136] The product II was centrifuged (10000 rpm for 5 min) and ultrasonically dispersed for 20 min to obtain the product III.

[0137] The product III was washed with ethanol and deionized water respectively until the pH was close to neutral, then dried at 60°C for 12 hours, and then placed in a muffle furnace at 600°C with a heating rate of 2°C / min. The product was calcined in an air atmosphere for 6 hours to remove the organic template and obtain a mesoporous silica solid powder.

[0138] S3, preparing nano-zeolite seeded silicon balls;

[0139] The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, wherein the solid-liquid mass ratio of the mesoporous silica solid powder to the polydimethyl diisopropyl ammonium chloride aqueous solution is 1:10. After gentle stirring and adsorption for 1 hour at room temperature, the powder is washed with deionized water and centrifuged three times (centrifuged at 10000 rpm for 5 minutes) to remove excess polycation electrolyte, thereby obtaining cation-modified mesoporous silica microspheres.

[0140] The modified mesoporous silica microspheres were immersed in a 1% nano-zeolite gel solution with a pH value of about 9.5, and gently stirred for 1 hour. After that, they were washed with 0.1 mol / L ammonia water and centrifuged 3 times (10000 rpm for 5 minutes), and then dried at 60°C to obtain nano-zeolite seeded silicon spheres.

[0141] S4, preparing adsorbent finished product II-multi-level porous zeolite microspheres II;

[0142] 0.1 g of the nano-zeolite seeded silicon spheres prepared in step S3 were placed in a clarified growth solution with a mass ratio of TPAOH:H2O:EtOH=0.75:7.77:1.48, and after hydrothermal treatment at 100°C for 1 day in a reactor, they were washed three times with 0.1 mol / L ammonia water and then washed twice with deionized water to obtain hollow zeolite microspheres.

[0143] Then, after drying at 100° C., the organic template is removed by calcining in a muffle furnace at 550° C. in an air atmosphere for 6 hours. The heating rate of the muffle furnace is 5° C. / min. The obtained solid powder product is the finished adsorbent II - multi-level porous zeolite microspheres II.

[0144] Example 3: Preparation of the adsorbent finished product III of the present invention - multi-level pore zeolite microspheres III, the preparation steps are as follows:

[0145] S1, preparing nano zeolite sol;

[0146] A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed, wherein the molar ratio of the tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=9:25:480:100.

[0147] The mixture was stirred vigorously at room temperature for 24 h to obtain a transparent colloidal solution, which was then refluxed in an oil bath at 100° C. for 36 h to obtain product I.

[0148] The obtained product I was repeatedly centrifuged (10000 rpm for 60 min), and finally ultrasonically dispersed for 20 min to obtain a zeolite colloidal solution with a mass fraction of about 4.0%, and the pH value was adjusted to about 9.5 with ammonia water for use.

[0149] S2, preparing mesoporous silica solid powder;

[0150] Weigh 90 mL of deionized water and 100 mL of isopropanol and mix them evenly at room temperature, add 1 g of hexadecylamine, dissolve it with ultrasound assistance, add 1.4 mL of 25%-28% ammonia water under stirring, and inject 5.8 mL of tetraethoxysilane at one time. Stop stirring after 30 seconds and let it stand at room temperature for 24 hours to obtain product II.

[0151] The product II was centrifuged (10000 rpm for 5 min) and ultrasonically dispersed for 20 min to obtain the product III.

[0152] The product III was washed with ethanol and deionized water respectively until the pH was close to neutral, then dried at 60°C for 12 hours, and then placed in a muffle furnace at 600°C with a heating rate of 2°C / min. The product was calcined in an air atmosphere for 6 hours to remove the organic template and obtain a mesoporous silica solid powder.

[0153] S3, preparing nano-zeolite seeded silicon balls;

[0154] The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, wherein the solid-liquid mass ratio of the mesoporous silica solid powder to the polydimethyl diisopropyl ammonium chloride aqueous solution is 1:10. After gentle stirring and adsorption for 1 hour at room temperature, the powder is washed with deionized water and centrifuged three times (centrifuged at 10000 rpm for 5 minutes) to remove excess polycation electrolyte, thereby obtaining cation-modified mesoporous silica microspheres.

[0155] The modified mesoporous silica microspheres were immersed in a 1% nano-zeolite gel solution with a pH value of about 9.5, and gently stirred for 1 hour. After that, they were washed with 0.1 mol / L ammonia water and centrifuged 3 times (10000 rpm for 5 minutes), and then dried at 60°C to obtain nano-zeolite seeded silicon spheres.

[0156] S4, preparing adsorbent finished product III-multi-level porous zeolite microspheres III;

[0157] 0.1 g of the nano-zeolite seeded silicon spheres prepared in step S3 were placed in a clarified growth solution with a mass ratio of TPAOH:H2O:EtOH=0.75:7.77:1.48, and after hydrothermal treatment at 150°C in a reactor for 1 day, they were washed 3 times with 0.1 mol / L ammonia water and then washed 2 times with deionized water to obtain hollow zeolite microspheres.

[0158] Then, after drying at 100° C., the organic template is removed by calcining in a muffle furnace at 550° C. in an air atmosphere for 6 hours. The heating rate of the muffle furnace is 5° C. / min. The obtained solid powder product is the finished adsorbent III-multi-level porous zeolite microspheres III.

[0159] Example 4: Preparation of the adsorbent finished product IV of the present invention - hierarchical pore zeolite microspheres IV, the preparation steps are as follows:

[0160] S1, preparing nano zeolite sol;

[0161] A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed, wherein the molar ratio of the tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=9:25:480:100.

[0162] The mixture was stirred vigorously at room temperature for 24 h to obtain a transparent colloidal solution, which was then refluxed in an oil bath at 100° C. for 36 h to obtain product I.

[0163] The obtained product I was repeatedly centrifuged (10000 rpm for 60 min), and finally ultrasonically dispersed for 20 min to obtain a zeolite colloidal solution with a mass fraction of about 4.0%, and the pH value was adjusted to about 9.5 with ammonia water for use.

[0164] S2, preparing mesoporous silica solid powder;

[0165] Weigh 90 mL of deionized water and 100 mL of isopropanol and mix them evenly at room temperature, add 1 g of hexadecylamine, dissolve it with ultrasound assistance, add 1.4 mL of 25%-28% ammonia water under stirring, and inject 5.8 mL of tetraethoxysilane at one time. Stop stirring after 30 seconds and let it stand at room temperature for 24 hours to obtain product II.

[0166] The product II was centrifuged (10000 rpm for 5 min) and ultrasonically dispersed for 20 min to obtain the product III.

[0167] The product III was washed with ethanol and deionized water respectively until the pH was close to neutral, then dried at 60°C for 12 hours, and then placed in a muffle furnace at 600°C with a heating rate of 2°C / min. The product was calcined in an air atmosphere for 6 hours to remove the organic template and obtain a mesoporous silica solid powder.

[0168] S3, preparing nano-zeolite seeded silicon balls;

[0169] The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, wherein the solid-liquid mass ratio of the mesoporous silica solid powder to the polydimethyl diisopropyl ammonium chloride aqueous solution is 1:10. After gentle stirring and adsorption for 1 hour at room temperature, the powder is washed with deionized water and centrifuged three times (centrifuged at 10000 rpm for 5 minutes) to remove excess polycation electrolyte, thereby obtaining cation-modified mesoporous silica microspheres.

[0170] The modified mesoporous silica microspheres were immersed in a 1% nano-zeolite gel solution with a pH value of about 9.5, and gently stirred for 1 hour. After that, they were washed with 0.1 mol / L ammonia water and centrifuged 3 times (10000 rpm for 5 minutes), and then dried at 60°C to obtain nano-zeolite seeded silicon spheres.

[0171] S4, preparing adsorbent finished product IV-multi-level porous zeolite microspheres IV;

[0172] 0.1 g of the nano-zeolite seeded silicon spheres prepared in step S3 were placed in a clarified growth solution with a mass ratio of TPAOH:H2O:EtOH=0.75:7.77:1.48, and after hydrothermal treatment at 100°C for 2 days in a reactor, they were washed three times with 0.1 mol / L ammonia water and then washed twice with deionized water to obtain hollow zeolite microspheres.

[0173] Then, after drying at 100° C., the organic template is removed by calcining in a muffle furnace at 550° C. in an air atmosphere for 6 hours. The heating rate of the muffle furnace is 5° C. / min. The obtained solid powder product is the finished adsorbent IV-multi-level porous zeolite microspheres IV.

[0174] Example 5: Preparation of the adsorbent finished product V-multi-level pore zeolite microspheres V of the present invention, the preparation steps are as follows:

[0175] S1, preparing nano zeolite sol;

[0176] A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed, wherein the molar ratio of the tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=9:25:480:100.

[0177] The mixture was stirred vigorously at room temperature for 24 h to obtain a transparent colloidal solution, which was then refluxed in an oil bath at 100° C. for 36 h to obtain product I.

[0178] The obtained product I was repeatedly centrifuged (10000 rpm for 60 min), and finally ultrasonically dispersed for 20 min to obtain a zeolite colloidal solution with a mass fraction of about 4.0%, and the pH value was adjusted to about 9.5 with ammonia water for use.

[0179] S2, preparing mesoporous silica solid powder;

[0180] Weigh 90 mL of deionized water and 100 mL of isopropanol and mix them evenly at room temperature, add 1 g of hexadecylamine, dissolve it with ultrasound assistance, add 1.4 mL of 25%-28% ammonia water under stirring, and inject 5.8 mL of tetraethoxysilane at one time. Stop stirring after 30 seconds and let it stand at room temperature for 24 hours to obtain product II.

[0181] The product II was centrifuged (10000 rpm for 5 min) and ultrasonically dispersed for 20 min to obtain the product III.

[0182] The product III was washed with ethanol and deionized water respectively until the pH was close to neutral, then dried at 60°C for 12 hours, and then placed in a muffle furnace at 600°C with a heating rate of 2°C / min. The product was calcined in an air atmosphere for 6 hours to remove the organic template and obtain a mesoporous silica solid powder.

[0183] S3, preparing nano-zeolite seeded silicon balls;

[0184] The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, wherein the solid-liquid mass ratio of the mesoporous silica solid powder to the polydimethyl diisopropyl ammonium chloride aqueous solution is 1:10. After gentle stirring and adsorption for 1 hour at room temperature, the powder is washed with deionized water and centrifuged three times (centrifuged at 10000 rpm for 5 minutes) to remove excess polycation electrolyte, thereby obtaining cation-modified mesoporous silica microspheres.

[0185] The modified mesoporous silica microspheres were immersed in a 1% nano-zeolite gel solution with a pH value of about 9.5, and gently stirred for 1 hour. After that, they were washed with 0.1 mol / L ammonia water and centrifuged 3 times (10000 rpm for 5 minutes), and then dried at 60°C to obtain nano-zeolite seeded silicon spheres.

[0186] S4, preparing adsorbent finished product V-multi-level pore zeolite microspheres V;

[0187] 0.1 g of the nano-zeolite seeded silicon spheres prepared in step S3 were placed in a clarified growth solution with a mass ratio of TPAOH:H2O:EtOH=0.75:7.77:1.48, and after hydrothermal treatment at 100°C for 3 days in a reactor, they were washed three times with 0.1 mol / L ammonia water and then washed twice with deionized water to obtain hollow zeolite microspheres.

[0188] Then, after drying at 100° C., the organic template is removed by calcining in a muffle furnace at 550° C. in an air atmosphere for 6 hours. The heating rate of the muffle furnace is 5° C. / min. The obtained solid powder product is the finished adsorbent V-multi-level pore zeolite microspheres V.

[0189] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to observe the surface morphologies of adsorbent finished products I, adsorbent finished products II, adsorbent finished products III, adsorbent finished products IV and adsorbent finished products V, so as to investigate the effects of different hydrothermal treatment temperatures (80°C, 100°C and 150°C) and different hydrothermal treatment times (1d, 2d and 3d) on the structure of the adsorbent finished products.

[0190] like Figure 7 As shown, the average particle size of the adsorbent product prepared by the present invention is about 1.3 μm, the particle size distribution is narrow, the dispersion is good, and it has a large hollow cavity. The average shell thickness is 0.2 μm. After the zeolite microcrystal layer is electrostatically assembled and hydrothermally treated, the smooth surface of the mesoporous silica microspheres becomes rough. Figure 6-Figure 8 It can be seen that different hydrothermal treatment temperatures did not affect the overall particle size and cavity characteristics of the finished adsorbent, but mainly affected the crystallization degree of silicalite-1 zeolite on the surface spherical shell and the morphology of mesoporous silica microspheres.

[0191] like Figure 6 As shown in the figure, under the same hydrothermal treatment time of 1d, the inner core of the mesoporous silica microspheres was not completely removed after the hydrothermal reaction at 80°C, and the silicate-1 in the shell was spherical and did not grow into blocky crystals for a second time. The silica in the inner core was not conducive to the diffusion of MTBE molecules in the subsequent adsorption process.

[0192] like Figure 7 As shown, when the hydrothermal treatment temperature is 100°C, the silicalite-1 nanoparticles on the shell layer of the finished adsorbent have grown into granular crystals of about 200 nm, and obvious coffin-type lattice fringes of MFI zeolite appear in the outer shell layer. Figure 7 The TEM electron microscope photo in the figure and the SEM electron microscope photo of the broken spherical shell clearly show that the adsorbent product prepared by the present invention at a hydrothermal treatment temperature of 100°C is a hollow spherical shell structure, and the zeolite layers of the shell are tightly combined. Figure 8 As shown, no complete microspheres were observed in the finished adsorbent product after treatment at 150°C, but a large number of spherical shell fragments appeared, which were interconnected. The reduction of diffusion channels was also not conducive to the subsequent adsorption process.

[0193] The effect of hydrothermal treatment time (1d, 2d, 3d) at 100°C on the structure of the finished adsorbent was further investigated. 1d of hydrothermal treatment time was sufficient (see Figure 7 ), if the time is too long, the formed zeolite microspheres will be damaged, resulting in a reduction in diffusion channels (see Fig. 9 and Fig.10 ).

[0194] In summary, it is finally determined that the optimal hydrothermal treatment temperature of the present invention is 100°C and the hydrothermal treatment time is 1 day.

[0195] Test Example 1:

[0196] An aqueous solution of methyl tert-butyl ether (MTBE) with an initial concentration of 100 mg / L was prepared using analytical grade methyl tert-butyl ether (MTBE).

[0197] Take 50 mg of each of the adsorbent materials, namely, silicalite-1 zeolite, the finished adsorbent prepared by the present invention, powdered activated carbon, synthetic resin (Amberlite XAD-4, Amberlite XAD-7) and mesoporous silica, and place them in separate centrifuge tubes. Add 10 mL of 100 mg / L MTBE solution to each centrifuge tube. Seal with polytetrafluoroethylene tape and place in a constant temperature oscillator at 20°C for 24 hours of oscillation adsorption to allow each adsorbent material to fully contact with MTBE to reach adsorption equilibrium.

[0198] After the reaction was completed, the adsorbent material in the centrifuge tube was centrifuged and 0.5 mL of MTBE supernatant sample was taken for gas chromatography analysis.

[0199] The MTBE supernatant sample was extracted before gas chromatography detection. 0.5 mL of butyl acetate was added to 0.5 mL of the MTBE supernatant sample and the mixture was extracted by vigorous shaking. After centrifugation at 15000 rpm for 3 min, 250 μL of ethyl acetate was taken and filtered with a 0.22 μm hydrophobic polytetrafluoroethylene (PTFE) syringe filter. Three parallel experiments were performed in all experiments, and the difference between the results of each parallel experiment was within 5%.

[0200] The results are as follows Fig.11 As shown in the figure, under the same conditions, the adsorbent product (S@MS) prepared in this test example has the best adsorption effect on MTBE, with a removal rate of 99.2%. The second is silicalite-1 zeolite, with a MTBE removal rate of 97.3%. Then comes Amberlite XAD-4, with a MTBE removal rate of 76.1%; the removal rate of MTBE by powdered activated carbon is 68.0%; the removal rate of MTBE by Amberlite XAD-7 is 21.6%; and finally, the removal rate of MTBE by mesoporous silica is 11.5%.

[0201] Test Example 2:

[0202] An aqueous solution of methyl tert-butyl ether with an initial concentration of 100 mg / L was used.

[0203] 50 mg of silicalite-1 zeolite and 50 mg of the finished adsorbent (S@MS) prepared by the present invention were placed in separate centrifuge tubes, and 10 mL of MTBE solution was added to each centrifuge tube. The centrifuge tubes were sealed and placed in a constant temperature oscillator at 20° C. for oscillation adsorption, and samples were taken at adsorption times of 1 h, 2 h, 3 h, 4 h, 6 h, 8 h, 12 h, 24 h and 30 h to determine the concentration of the remaining MTBE in the solution.

[0204] All experiments were conducted in triplicate, and the differences between the results of each parallel experiment were within 5%.

[0205] The results are as follows Fig.12As shown, the adsorption of MTBE by silicalite-1 zeolite and the finished adsorbent (S@MS) prepared in this test example went through a rapid stage, a medium stage and a slow stage. The rapid adsorption stage can be completed within the first 2 hours of adsorption, reaching more than 80% of the entire adsorption process; then the adsorption process entered the buffer stage, and the adsorption rate dropped significantly. The difference is that the silicalite-1 zeolite reaches equilibrium after 24 hours of adsorption, and the residual concentration of MTBE in the solution remains basically unchanged, while the finished adsorbent prepared by the present invention can reach equilibrium after 12 hours of adsorption.

[0206] Test Example 3:

[0207] An aqueous solution of methyl tert-butyl ether with an initial concentration of 100 mg / L was used.

[0208] Take 50 mg of silicalite-1 zeolite and the finished adsorbent prepared by the present invention into a centrifuge tube, and add 10 mL of MTBE solution. After sealing the centrifuge tube, place it in a constant temperature oscillator at 20°C for oscillation adsorption. When the adsorption time of silicalite-1 zeolite is 24 hours and the adsorption time of the finished adsorbent prepared by the present invention is 12 hours, take samples to determine the concentration of the remaining MTBE in the solution. Then, the silicalite-1 zeolite and the finished adsorbent prepared by the present invention are placed in a muffle furnace and calcined at 500°C for 6 hours for desorption and regeneration, and then the adsorption experiment is repeated and calcined and desorbed again, and repeated 6 times.

[0209] All experiments were conducted in triplicate, and the differences between the results of each parallel experiment were within 5%.

[0210] After repeated use for 6 times, the adsorption capacity of MTBE by silicalite-1 zeolite and the finished adsorbent prepared by the present invention decreased from the initial 24.89 mg / g and 27.75 mg / g to 21.69 mg / g and 25.85 mg / g. After high-temperature calcination and regeneration for 6 times, the adsorption capacity of MTBE by silicalite-1 zeolite and the finished adsorbent prepared by the present invention was 87.14% and 93.15% of the initial adsorption capacity, respectively.

[0211] In summary, the adsorbent prepared by the present invention has a multi-level pore structure and nano-zeolite seeds, has excellent adsorption performance and stability, and can be reused. Therefore, the adsorbent has broad application prospects in the field of groundwater pollution control, and is mainly used for the adsorption and remediation of pollutants such as heavy metals, organic matter, and pesticides in groundwater.

[0212] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing an adsorbent for groundwater remediation, characterized in that: The following steps are involved: S1, preparing nano zeolite sol; A certain amount of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol are mixed and vigorously stirred at room temperature to obtain a transparent colloidal solution, which is then placed in an oil bath and refluxed at 90-110° C. for 30-40 hours to obtain product I. The obtained product I is repeatedly centrifuged and finally ultrasonically dispersed to obtain a zeolite colloidal solution, and the pH value is adjusted to 9-10 for use; S2, preparing mesoporous silica solid powder; Weigh a certain amount of deionized water and isopropanol, mix them evenly at room temperature, add a certain amount of hexadecylamine, dissolve them with ultrasound assistance, add a certain amount of ammonia water under stirring, and inject a certain amount of tetraethoxysilane at one time, stop stirring after 30 seconds, and let stand at room temperature for 24 hours to obtain product II; The product II is centrifuged and ultrasonically dispersed to obtain the product III, the product III is washed until the pH value is nearly neutral, then dried at 60° C. for 12 h, and then placed in a muffle furnace at 600° C. and calcined in an air atmosphere for 6 to 8 h to remove the organic template, thereby obtaining a mesoporous silica solid powder; S3, preparing nano-zeolite seeded silicon balls; The mesoporous silica solid powder prepared in step S2 is placed in a 0.3% polycation electrolyte polydimethyl diisopropyl ammonium chloride aqueous solution, and after gentle stirring and adsorption for 1 to 2 hours at room temperature, it is washed with deionized water and centrifuged several times to remove excess polycation electrolyte to obtain cation-modified mesoporous silica microspheres; The modified mesoporous silica microspheres were immersed in a 1% nano-zeolite gel solution, gently stirred for a period of time, washed with 0.1 mol / L ammonia water and centrifuged several times, and then dried at 60°C to obtain nano-zeolite seeded silica spheres; S4, preparing finished adsorbent product - hierarchical pore zeolite microspheres; A certain amount of nano-zeolite seeded silicon balls prepared in step S3 are placed in a certain amount of clarified growth liquid with a mass ratio of TPAOH:H2O:EtOH=0.6-0.8:7-8:1.3-1.5, and after hydrothermal treatment at a certain temperature in a reactor for a certain time, they are washed multiple times with 0.1 mol / L ammonia water, and then washed multiple times with deionized water to obtain hollow zeolite microspheres. After drying at 100°C, they are calcined in a muffle furnace at 550°C in an air atmosphere for 6 hours to remove the organic template, and the obtained solid powder product is the finished adsorbent product - hierarchical pore zeolite microspheres.

2. The method for preparing an adsorbent for groundwater remediation according to claim 1, characterized in that: In step S1, the molar ratio of tetrapropylammonium hydroxide, tetraethoxysilane, deionized water and ethanol is TPAOH:TEOS:H2O:EtOH=8-10:20-30:450-550:80-120.

3. The method for preparing an adsorbent for groundwater remediation according to claim 2, characterized in that: In step S1, the duration of the vigorous stirring at room temperature is 20 to 30 hours.

4. The method for preparing an adsorbent for groundwater remediation according to claim 3, characterized in that: In step S1, the rotation speed of the centrifugal separation is 8000-12000 rpm, the centrifugal time is 40-90 min; the ultrasonic dispersion time is 15-30 min.

5. The method for preparing an adsorbent for groundwater remediation according to claim 4, characterized in that: In step S1 , the pH value of the zeolite colloidal solution is adjusted using aqueous ammonia.

6. The method for preparing an adsorbent for groundwater remediation according to claim 1, characterized in that: In step S2, the volume ratio of the deionized water to isopropyl alcohol is 1:1-1.

2.

7. The method for preparing an adsorbent for groundwater remediation according to claim 6, characterized in that: In step S2, the mass fraction of the ammonia water is 25% to 28%.

8. The method for preparing an adsorbent for groundwater remediation according to claim 7, characterized in that: In step S2, the pH value of the product III is adjusted using ethanol and deionized water.

9. The method for preparing an adsorbent for groundwater remediation according to claim 8, characterized in that: In step S2, the heating rate of the muffle furnace is 2°C / min; in step S4, the heating rate of the muffle furnace is 5°C / min.

10. The method for preparing an adsorbent for groundwater remediation according to claim 9, characterized in that: In step S3, the solid-to-liquid mass ratio of the mesoporous silica solid powder to the polydimethyldiisopropylammonium chloride aqueous solution is 1:

10.

11. The method for preparing an adsorbent for groundwater remediation according to claim 1, characterized in that: In step S3, the pH value of the nano-zeolite colloid is 9.

5.

12. The method for preparing an adsorbent for groundwater remediation according to claim 1, characterized in that: In step S4, the temperature of the hydrothermal treatment is 80-150° C., and the duration is 1-3 days.

Citation Information

Patent Citations

  • Method for preparing mixed charcoal-based adsorption material for underground water repairing

    CN110586033A

  • Adsorbing material for removing lead, copper and cadmium in underground water and preparation method and application thereof

    CN112755962A

  • Adsorption material for removing nitrate in underground water as well as preparation method and application of adsorbing material

    CN113181886A

  • Method for preparing zeolite material in perforation type of multilevel pore canals

    CN101003377A

  • MFI zeolite adsorbent containing hierarchical pores as well as preparation method and application of MFI zeolite adsorbent

    CN116510685A